Graft anastomosis technique in the fragile aorta. (October 2013) - Higuchi, Kazuhiko; Takamoto, Shinichi
Here, we describe a technique for creating a secure anastomosis between a graft and the stump of the aorta, involving the fragile aortic wall between the folded flap of the graft inside the aorta and a Teflon felt strip outside.